2022
DOI: 10.1021/acsomega.2c03410
|View full text |Cite
|
Sign up to set email alerts
|

Modified Peanut Shell as an Eco-Friendly Biosorbent for Effective Extraction of Triazole Fungicide Residues in Surface Water and Honey Samples before Their Determination by High-Performance Liquid Chromatography

Abstract: An eco-friendly sample preparation method that is based on the use of a modified peanut shell as an efficient biosorbent for the extraction of triazole residues before their analysis by high-performance liquid chromatography was reported. The four triazole fungicides were separated on a Purospher STAR RP-18 endcapped (4.6 × 150 mm, 5 μm) column with a mobile phase of 50% (v/v) acetonitrile at a flow rate of 1.0 mL min –1 and detection wavelength set at 220 nm. Peanut shells modified by d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The feature peaks at 1602 cm −1 of the three samples are similar, showing that the content of lignin is the same. 43,44 Fig. 4b exhibits the FTIR spectra of the magnetic biochars, which revealed a peak at 580 cm −1 that was identied as the Fe-O vibration.…”
Section: Resultsmentioning
confidence: 99%
“…The feature peaks at 1602 cm −1 of the three samples are similar, showing that the content of lignin is the same. 43,44 Fig. 4b exhibits the FTIR spectra of the magnetic biochars, which revealed a peak at 580 cm −1 that was identied as the Fe-O vibration.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been done to examine the capacity of peanut shell powder to remove various reactive colors such as Green 19, Orange 16, and Yellow 14from aqueous solutions (Nadi et al, 2012;Wu et al, 2019;Garget al, 2019). More than 90% of these dyes have been adsorbed from the wastewater by using peanut shell powder (Garget al, 2019;Herbert et al, 2021;Pączkowski et al, 2021;Khiaophong et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Peanut shells and rice husks are two examples of agricultural wastes that can be used as a lowcost biosorbent for dyes in water. Peanut shells contain high cellulose, hemicellulose, and lignin (Khiaophong et al, 2022;Sah et al, 2022). Some studies have reported the ability of activated carbon derived from peanut shells to remove aqueous pollutants, including dye.…”
Section: Introductionmentioning
confidence: 99%